Perforated Colon Ulcer induced by Nonsteroidal Anti-Inflammatory Drugs - Sakimura, Chika; Murata, Yoko; Iwamoto, Akemi; Kimura, Osamu; Yamane, Nariyuki; Hamazoe, Ryuichi (Nippon Shokaki Geka Gakkai zasshi, 2008)
We report the rare case of a 59-year-old man suffering a perforated colon ulcer induced by nonsteroidal antiinflammatory drugs (NSAIDs). Diclofenac sodium tablets admitted at 75mg/day were administrated for lumbago due to spinal canal stenosis. After six days, the man experienced anorexia, abdominal fullness, and upper right abdominal pain. Physical examination showed signs of peritoneal irritation. Based on a diagnosis of diffuse suppurative peritonitis, we conducted emergency transverse colectomy, finding two perforated ulcer sites and one non-perforated ulcer at the resected transverse colon. Histological examination showed nonatypical cells in the mucosal tissue around the ulcers. It is thus important to bear colon disease mind when NSAIDs are administered as a painkiller.